Answers

  • Brainly User
2016-07-14T09:29:32+08:00
If the leading coefficient (a) is 1, factor the constant (c) is such a way that the sum of the factors  is equal to the middle term coefficient (b) of the equation.

Standard form :  ax² + bx + c = 0
Where a is the leading coefficient, b is the middle term's coefficient, and c is the constant.

Example:

x² + 10x + 24 = 0

a =1 (leading coefficient);  b = 10;   c = 24

Factors of 24 (c) are:

a)  (8) and (3) ⇒  8 + 3 = 11 (11 is not equal to 10)

b)  (12) and (2) ⇒  12 + 2 = 12  (12 is not equal to 10)

c)  (6) and (4) ⇒  6 + 4 = 10  (10 is equal to 10)

Therefore the factors of constant is (6) and (4), and the factors of the quadratic equation x² + 10x + 24 = 0 is:

(x + 6) (x + 4) = 0

0